(untitled) (Archives of Clinical Psychiatry, 2009)
Depression is the most common psychiatric disorder in patients with cancer, with prevalence rates ranging from 22% to 29%. This variability is associated to cancer sites, clinical stages, pain, limited physical functioning, beyond the existence of social support. Depression is associated to poorer prognosis and higher cancer mortality. Depressive syndromes can be a consequence of the antineoplasic therapies, as occurs in 21% to 58% of the patients treated with alfa-interferon. Sadness and desperation can inhibit the search for care by the patients, and difficult depression recognition. Antidepressant treatment is effective, and improve the adherence to cancer treatments, reducing side effects as nausea, pain and fatigue. In cancer patients, pretreatment with antidepressants seems to minimize depressive symptoms induced by interferon-alfa. Psychosocial interventions as relaxing techniques, group and individual psychotherapies can also be applied to reduce depressive and stress symptoms in patients with cancer.